1976
DOI: 10.1246/bcsj.49.2645
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Conversion of Methoxyketene Intermediate into Methyl Ester in the Photolysis of 2-Methoxy-3-dijphenylmethyl-4-diphenylmethylene-2-cyclobuten-1-one

Abstract: The photolysis of methylenecyclobutenone in the presence of benzophenone or oxygen affords the one carbon diminished product, methyl 4,4-diphenyl-2-diphenylmethyl-2,3-butadienoate. The reaction pathway is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…When the cyclization of allenic carboxylic acid esters to halogenated lactones by addition of bromine was discovered in the mid‐seventies, it was demonstrated soon after that oxaphospholenes could be synthesized from the corresponding allenylphosphonates . Thanks to the discovery by Mark and Boisselle in 1962 of the [2,3]‐sigmatropic rearrangement which occurs after treatment of propargylic alcohols 86 with diethyl chlorophosphites, a very convenient synthesis of allenylphosphonate precursors 87 was available.…”
Section: Synthetic Routes Towards Oxaphospholenes and Benzoxaphospholmentioning
confidence: 99%
“…When the cyclization of allenic carboxylic acid esters to halogenated lactones by addition of bromine was discovered in the mid‐seventies, it was demonstrated soon after that oxaphospholenes could be synthesized from the corresponding allenylphosphonates . Thanks to the discovery by Mark and Boisselle in 1962 of the [2,3]‐sigmatropic rearrangement which occurs after treatment of propargylic alcohols 86 with diethyl chlorophosphites, a very convenient synthesis of allenylphosphonate precursors 87 was available.…”
Section: Synthetic Routes Towards Oxaphospholenes and Benzoxaphospholmentioning
confidence: 99%
“…Later, the same group demonstrated that, upon ring‐opening, the allene–ketene intermediate 82 could undergo a rapid [2+2] cycloaddition with benzophenone to afford an oxetanone intermediate, which eventually led to product 83 after a concomitant elimination of diphenylketene 84 (Scheme ) . A similar transformation was realized under an oxygen atmosphere with elimination of carbon dioxide, albeit with a lower yield.…”
Section: Photolysis‐induced Ring Openingmentioning
confidence: 99%
“…(Scheme28). [36] As imilart ransformation was realized under an oxygen atmospherew ith elimination of carbon dioxide,a lbeit with alower yield. In 1984, Schiess et al reported the cycloaddition of benzocyclobutenone 85 (Scheme 29) with variousd ienophiles under flash photolysis conditions.…”
Section: Photolysis-induced Ring Openingmentioning
confidence: 99%
“…The photolysis of methylenecyclobutenone in the presence of benzophenone or oxygen afforded an a-allenic ester resulting from the cycloaddition reaction of the methoxyketene intermediate (Scheme 23). 49 Scheme 23…”
Section: From Methylenecyclobutanonementioning
confidence: 99%